ANGKA KONVEKSI TERMAL ALIRAN FLUIDISI PADA TABUNG HORISONTAL DAN ANGKA REYNOLDS RENDAH - Pawito M Sontowiro (Mesin, 1998)
A ï¬‚uidized bed is a bed comprises a mixture of solid particles suspension in stream of gas. The heat transfer phenomenon between the surface of immersed body to/from ï¬‚uidized bed is very complicated mechanism. Aside from the governing variables on conventional convective heal transfer, the rate of heat transfer coefficient in ï¬‚uidized bed, is also inï¬‚uenced by physical and geometrical properties of solid particle. One of the variables which governs the value of thermal convective heat transfer coeï¬icient is voidage. The inï¬‚uence of voidage on thermal convective heat transfer coefficient at low Reynolds number will be reported on this paper.